Pelatihan Pembuatan Immunomodulatory Drink Kombucha untuk Meningkatkan Perekonomian Masa New Normal pada Masyarakat Desa Majau dan Kadudampit Kecamatan Saketi Kabupaten Pandeglang, Banten - Swastika Oktavia; Cory Novi; Ega Egriana Handayani; Nurullah Asep Abdilah; Usman Setiawan; Firman Rezaldi (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING ON MAKING KOMBUCHA IMMUNOMODULATORY DRINK TO IMPROVE THE ECONOMY OF THE COMMUNITY OF MAJAU AND KADUDAMPIT VILLAGES, SAKETI DISTRICT, PANDEGLANG REGENCY, BANTEN IN THE NEW NORMAL ERA. Immunomodulatory drink are in great demand and needed by people in the new normal era. One such drink is kombucha. Kombucha is a drink from bioprocess technology that is fermented using microbes, namely a combination of bacteria and yeast as the initial culture. Many activities that support the health aspects of the new normal have been carried out. However, health activities that support economic aspects have never been implemented during this new normal period, especially in Majau and Kadudampit Villages. The purpose of this activity was as a means of socialization and training for the manufacture of fermented kombucha drinks which can be used as an immune enhancer but also commercialized, especially to improve the economic sector of the community. The method used includes preparation of the training venue, filling in participant attendance and questionnaires, opening training events, implementing and training in making kombucha drinks with various stages, namely the stages of making kombucha, the kombucha fermentation process, the kombucha harvest process, and the dosage and how to consume kombucha. Based on the results of training activities both carried out in Majau and Kadudampit Villages showed that information on the use of kombucha in increasing immunity and the economy in the new normal era was largely unknown to the people in the two villages. This was because people were more familiar with other fermented products, namely yogurt and yakult.